Rare genetic variation in mitochondrial pathways influences the risk for Parkinson's disease - Gaare, Johannes J. (Mov Disord, 2018)
Background: Mitochondrial dysfunction plays a key role in PD, but the underlying molecular mechanisms remain unresolved. We hypothesized that the disruption of mitochondrial function in PD is primed by rare, protein‐altering variation in nuclear genes controlling mitochondrial structure and function. Objective: The objective of this study was to assess whether genetic variation in genes associated with mitochondrial function influences the risk of idiopathic PD. Methods: We employed whole‐exome sequencing data from 2 independent cohorts of clinically validated idiopathic PD and controls, the Norwegian ParkWest cohort (n = 411) and the North American Parkinson's Progression Markers Initiative (n = 640). We applied burden‐based and variance‐based collapsing methods to assess the enrichment of rare, nonsynonymous, and damaging genetic variants on genes, exome‐wide, and on a comprehensive set of mitochondrial pathways, defined as groups of genes controlling specific mitochondrial functions. Results: Using the sequence kernel association test, we detected a significant polygenic enrichment of rare, nonsynonymous variants in the gene‐set encoding the pathway of mitochondrial DNA maintenance. Notably, this was the strongest association in both cohorts and survived multiple testing correction (ParkWest P = 6.3 × 10(−3), Parkinson's Progression Markers Initiative P = 6.9 × 10(−5), metaanalysis P = 3.2 × 10(−6)). Conclusions: Our results show that the enrichment of rare inherited variation in the pathway controlling mitochondrial DNA replication and repair influences the risk of PD. We propose that this polygenic enrichment contributes to the impairment of mitochondrial DNA homeostasis, thought to be a key mechanism in the pathogenesis of PD, and explains part of the disorder's “missing heritability.” © 2018 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society